2008
DOI: 10.1097/iae.0b013e3181744153
|View full text |Cite
|
Sign up to set email alerts
|

Radial Optic Neurotomy for Central Retinal Vein Occlusion

Abstract: RON may improve visual acuity in some eyes with CRVO, but complications are common. In our series, surgery by itself did not seem to improve the outcome of CRVO when compared with its natural history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Radial neurotomy has been suggested as a therapy for CRVO [110,111,112,113]. However, randomized prospective trials have not yet shown beneficial effects of radial neurotomy in the treatment of CRVO, so that it is unclear whether the technique should be recommended [86].…”
Section: Surgical Approaches To Treating Rvomentioning
confidence: 99%
See 2 more Smart Citations
“…Radial neurotomy has been suggested as a therapy for CRVO [110,111,112,113]. However, randomized prospective trials have not yet shown beneficial effects of radial neurotomy in the treatment of CRVO, so that it is unclear whether the technique should be recommended [86].…”
Section: Surgical Approaches To Treating Rvomentioning
confidence: 99%
“…RON has been associated with a potential risk of laceration of the central retinal artery or central retinal vein, optic nerve fiber damage with visual field loss, globe perforation, retinal detachment, choroidal neovascularization at the neurotomy site, and anterior segment neovascularization [110,113,120]. The PACORES (Pan-American Collaborative Retina Study) Group evaluated the complications after RON for CRVO [110].…”
Section: Surgical Approaches To Treating Rvomentioning
confidence: 99%
See 1 more Smart Citation
“…Various medical and surgical interventions have been tried, including argon laser panretinal photocoagulation (Hayreh 1990), macular grid photocoagulation (CVOS Group 1995), tissue plasminogen activator (Everett 2006), oral pentoxifylline (Park 2007), hyperbaric oxygen therapy (Wright 2007), radial optic neurotomy (Arevalo 2008; Hasselbach 2007; Opremcak 2006; Zambarakji 2005) and pars plana vitrectomy with internal limiting membrane peeling (DeCroos 2009; Park 2010; Raszewska-Steglinska 2009), but these have not been successful. More recently, an RCT comparing laser-induced chorioretinal venous anastomosis to sham treatment in adults with non-ischemic CRVO-ME of three to twelve months duration demonstrated moderate efficacy, especially in the 76% who developed a functioning anastomosis following laser treatment, and the visual acuity advantage compared to control was maintained at 18 months (McAllister 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other possible complications of this procedure are laceration of central retinal artery or vein, globe perforation, retinal detachment, vitreous hemorrhage, neovascular glaucoma, or choroidal neovascularization (CNV) [36, 41, 42]. Consequently, benefits of RON appear to be controversial and its efficacy remains to be proven in prospective, RCTs.…”
Section: Surgical Optionsmentioning
confidence: 99%